Pengaruh Tayangan Sepakbola Terhadap Kedekatan Personal terhadap Komunitas Ayam Kinantan - Muhammad Zidan Sayrevi; Abdul Rahman; Maulana Adinata Dalimunthe (Institut Nalanda, 2024)
In this era of globalization, mass media has a very significant role in shaping people's behavior and preferences. One of the most popular forms of media is football broadcasts. Football is not just a sport, but also a social phenomenon that can unite various groups and form strong communities. In the midst of community life, there are small groups that are often formed through shared interests and hobbies, one of which is the Kinantan Chicken community. This research aims to investigate the influence of football broadcasts on the personal closeness of members of the Kinantan Chicken Community. Quantitative methods are used by distributing questionnaires to community members who actively watch football broadcasts. It is hoped that the results of statistical data analysis will reveal whether exposure to football broadcasts has a positive impact on personal relationships in the context of the community. The results of this research can provide insight into how football broadcasts can influence personal closeness and interactions within a community. Through quantitative research, we assess the extent to which football viewing intensity can influence interpersonal relationships in these communities. The analysis shows a positive correlation between the frequency of watching football and the level of personal closeness. These findings confirm that football broadcasts are not only entertainment, but also play an important role in forming emotional bonds in a community context. The implications of the results of this research can be a basis for developing strategies to increase personal closeness in the community concerned.